Global Epidemiology of Ischemic Heart Disease: Results from the Global Burden of Disease Study - Khan, Moien AB; Hashim, Muhammad Jawad; Mustafa, Halla; Baniyas, May Yousif; Al Suwaidi, Shaikha Khalid Buti Mohamad; AlKatheeri, Rana; Alblooshi, Fatmah Mohamed Khalfan; Almatrooshi, Meera Eisa Ali Hassan; Alzaabi, Mariam Eisa Hazeem; Al Darmaki, Reem Saif; Lootah, Shamsa Nasser Ali Hussain (Curēus (Palo Alto, CA), 2020)
BackgroundIschemic heart disease (IHD) is a leading cause of death worldwide. Also referred to as coronary artery disease (CAD) and atherosclerotic cardiovascular disease (ACD), it manifests clinically as myocardial infarction and ischemic cardiomyopathy. This study aims to evaluate the epidemiological trends of IHD globally.MethodsThe most up-to-date epidemiological data from the Global Burden of Disease (GBD) dataset were analyzed. GBD collates data from a large number of sources, including research studies, hospital registries, and government reports. This dataset includes annual figures from 1990 to 2017 for IHD in all countries and regions. We analyzed the incidence, prevalence, and disability-adjusted life years (DALY) for IHD. Forecasting for the next two decades was conducted using the Statistical Package for the Social Sciences (SPSS) Time Series Modeler (IBM Corp., Armonk, NY).ResultsOur study estimated that globally, IHD affects around 126 million individuals (1,655 per 100,000), which is approximately 1.72% of the world’s population. Nine million deaths were caused by IHD globally. Men were more commonly affected than women, and incidence typically started in the fourth decade and increased with age. The global prevalence of IHD is rising. We estimated that the current prevalence rate of 1,655 per 100,000 population is expected to exceed 1,845 by the year 2030. Eastern European countries are sustaining the highest prevalence. Age-standardized rates, which remove the effect of population changes over time, have decreased in many regions.ConclusionsIHD is the number one cause of death, disability, and human suffering globally. Age-adjusted rates show a promising decrease. However, health systems have to manage an increasing number of cases due to population aging.